If xy1 = 0 then prove that x3 y3 1 =3xy
Answers
Answered by
3
HEY!!
if x+y+1 = 0 then prove that x3 + y3 + 1 =3xy
we know x+y+1=0
then x+y = -1
x+y+1 = 0
(x+y)3 = (-1)3
x3 + y3 +3xy(x+y) = -1
x3 +y3 +3xy(-1) = -1
x3 +y3 - 3xy = -1
x3 + y3 +1 = 3xy
It is proveed
if x+y+1 = 0 then prove that x3 + y3 + 1 =3xy
we know x+y+1=0
then x+y = -1
x+y+1 = 0
(x+y)3 = (-1)3
x3 + y3 +3xy(x+y) = -1
x3 +y3 +3xy(-1) = -1
x3 +y3 - 3xy = -1
x3 + y3 +1 = 3xy
It is proveed
Answered by
2
Here is your answer
------------------------------------
we know x+y+1=0
--------------------------------------
= x+y = -1
= x+y+1 = 0
--------------------------------
=> (x+y)3 = (-1)3
=> x3 + y3 +3xy(x+y)
=> -1
________________
=> x3 +y3 +3xy(-1) = -1
=> x3 +y3 - 3xy = -1
=> x3 + y3 +1 = 3xy
------------------------------------
we know x+y+1=0
--------------------------------------
= x+y = -1
= x+y+1 = 0
--------------------------------
=> (x+y)3 = (-1)3
=> x3 + y3 +3xy(x+y)
=> -1
________________
=> x3 +y3 +3xy(-1) = -1
=> x3 +y3 - 3xy = -1
=> x3 + y3 +1 = 3xy
Similar questions